Utilização do “Phage Display” para a identificação de peptídeos reconhecidos por Imunoglobulinas Y Policlonais anti-proteínas totais de larvas do Boophilus microplus - Prudencio, Carlos Roberto (2004)
Peptides were selected by polyclonal IgY specific for Boophilus microplus larval stage total proteins using a library of synthetic peptides presented in phages. Initially, for the production of polyclonal serum, chickens were immunized with total parasite larval stage proteins. Screening was monitored by ELISA during the injection period to confirm the development of immune response. After obtaining a satisfactory titer, the immunoglobulins were precipitated and partially characterized. The process of obtaining immunoglobulins from chicken serum was satisfactory and polyclonal antibodies were functionally active for recognition of total antigens. Subsequently, a peptide library fused to phage capsid Protein III was screened against polyclonal Y immunoglobulin purified by immunogen affinity. All peptides were recognized by tick anti-protein antibodies and the antigenicity of each peptide was deduced by bioinformatics. The consensus sequences NxxxKxxL and TPDKS were identified in 65% and 12% of sequenced phages, respectively. Similar sequences have been identified between peptides and B. microplus proteins deposited in the GENEBANK. Through the selection process it was possible to identify probable protein targets. Therefore, animal immunization tests are being developed to determine the immune response generated by the peptides obtained in this work.